PERANCANGAN APLIKASI MOBILE KALKULASI DRILL ASSEMBLY OFFSET (DAO) PENGEBORAN SUMUR MINYAK BERBASIS ANDROID - Ratuwulan, Anjelis; Yamin, Muhammad Ikrar; Saromah, Saromah; Setiawan, Adi Wahyu; Mahfuzan, Muhammad Saqfan (STKIP Persada Khatulistiwa Sintang, 2024)
The advancement of mobile technology has significantly contributed to various industries, including the oil and gas industry. In this context, mobile applications have become extremely useful tools for facilitating the planning and execution of oil well drilling operations. This study explores the design and implementation of a Mobile Application for Drill Assembly Offset Calculation based on Android. This application aims to provide an easy-to-use and efficient solution for engineers and technicians involved in oil well drilling. The main features of this application include offset calculations to align drilling equipment with the targeted well, accurate calculations to minimize risks and enhance operational efficiency, and intuitive data visualization. Through the integration of mobile technology, users can quickly access and utilize this tool in the field, reducing dependence on specialized hardware and increasing flexibility. Thus, it is hoped that this application can improve the effectiveness, efficiency, and safety of oil well drilling operations, and contribute positively to overall industry productivity.